PEMETAAN TOPOGRAFI PADA PERUMAHAN ANDALUSIA DUSUN SUCI KECAMATAN MANYAR KABUPATEN GRESIK - Muhammad Firdaus Al Farabi (Jurnal Vokasi Teknik Sipil, 2024)
Land surveying is essential in supporting a variety of modern construction projects, including in mapping and positioning housing projects. The measurement technique with the GPS-equipped Total Station allows the collection of accurate coordinate data through the polygon method, which is necessary in residential plot mapping or stakeout. This method includes collecting field coordinate data with Total Station and GPS, then data processing using Civil 3D to produce accurate topographic maps. This study aims to produce topographic maps and stakeout data in Andalusia Gresik housing. Measurements in Andalusia Housing using the Topcon GTS-230N Total Station showed a discrepancy between the measured land boundary and the siteplan map, which was then corrected by cutting roads to maximize land use. One plot measuring 7 x 12 m cannot be pegged because it exceeds the land limit set in the site plan. The elevation results indicate a height difference of ±0.3 m from the road and the existence of a mound as high as ±1.4 m. The resulting topographic map shows one meeting hall and 42 plots of houses of various sizes. Keywords: Land Survey, Total Station, Civil 3D, Topographic Map, and Siteplan